Development and validation of the Nottingham Auditory Milestones (NAMES) profile for deaf children under 2 years old, using cochlear implants - Datta, Gill; Kitterick, Pádraig T.; Ramirez-Inscoe, Jayne (Taylor & Francis, 2018)
Objectives: Clinicians face considerable challenges in setting appropriate auditory goals for babies and young children who receive cochlear implants. This paper describes the rationale, organisation, implementation and validation of the Nottingham Auditory Milestones profile that was developed to address these challenges.